Marketingová strategie pro hotel Panská lícha - Zábrž, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Cílem této diplomové práce je navržení vhodné marketingové strategie pro Hotel Pánská lícha. Teoretická část obsahuje vysvětlení základních pojmů v oblasti marketingové strategie. Praktická část se zabývá analýzou současného stavu firmy, která slouží jako podklad pro návrh marketingové strategie firmy. Výsledkem je doporučení návrhů a jejich přínos pro firmu.

The aim of this master’s thesis is the suggestion of marketingstrategy for Hotel Panská lícha. The theoretical part contains an explanation of basic concepts of marketingstrategy. The practical part is concerned with analysisof the current situation of the company whichservesas a basisfor suggestingmarketing strategies. The result is a summary of measures and proposals, includingtheir benefitsfor the company.
Marketing Strategy for hotel Panská lícha
Keywords: Marketing; strategie; marketingová strategie; zákazník; služba; konkurence; cena; analýza; trh.; Marketing; strategy; marketing strategy; customer; service; competition; price; analysis; market.